Effects of soil pH on nutrient concentration and dry matter partitioning of Magnifera indica cv Harumanis seedling grown under high temperature conditions - Jamil, Nor Azlina; Hassan, Siti Aishah; Ding, Phebe; I., Roslan (Faculty of Computer Science and Information Technology, Universiti Putra Malaysia, 2015)
A study on the uptake of selected essential elements and biomass partitioning as affected by soil pH of Magnifera indica cv Harumanis seedling grown in calcareous soil under dry and high temperature conditions was carried out. Seedlings were grown in polybags containing slightly acid to normal pH, 5.9-7.0 and high pH, 7.0-8.1 soils which obtained from Ladang Harumanis Bukit Bintang, Sungai Batu Pahat, Perlis. Soil was analyzed for chemical and physical characteristics. After 4 months, biomass and nutrient concentration in leaf tissues were determined. The soil with high pH had low CEC, N, Mg, K but high in Ca and EC. The chemical and physical properties of the soil directly influenced the nutrient uptake of the plants. Calcium, phosphorous and boron concentrations in plant were significantly reduced for seedlings grown in high soil pH. However Zn and Mn content in leaves was increased compared to lower soil pH. Root growth was significantly reduced at high pH, by 28% reduction whereas for leaves and stem by 38% and 30% respectively, compared to lower soil pH. However, among pH ranges, no significant effect on root to shoot ratio was found. Calcareous soils should be treated to lower the pH for mango production.